Criminality, Substance abuse and Problematic Family Relations in Adolescence - Valeria Saladino; Lilli Hoelzlhammer; Valeria Verrastro (Journal of Addiction Medicine and Therapeutic Science - Peertechz Publications, 2020)
Adolescence is characterized by high level of psychosocial vulnerabilities. It is a developmental phase in which youths explore themselves, others, and their social context. At the same time, the physical, behavioral and cognitive changes influence the self-image of adolescents. In addition, risk-taking and sensation-seeking are common and often associated with the engagement in risky or transgressive behaviors. During adolescence, aggressive conduct or use of substance may symbolise a need of control. Adolescents often behave aggressively to achieve their autonomy and self-identity from the family system. Criminological and developmental psychology's theories focus on these behaviors and consider individual, family and environmental factors from a multifactorial point of view. This brief article shows some considerations about the relationship between criminality, substance abuse and family system in youths' development.